Hepatoprotective effect of Paederia foetida on paracetamol-induced hepatobiliary disease in rats via alteration of inflammatory and Nrf2/HO-1 pathway - Zhenzhen Feng; Jianyin Li (Acta Cirúrgica Brasileira)
ABSTRACT Purpose: To scrutinize the hepatoprotective effect of Paederia foetida against paracetamol-induced hepatobiliary in rats. Methods: Rats were received the oral administration of paracetamol (3 mg/kg) empty stomach for the induction of hepatobiliary in rats except normal rats. the rats were received the oral administration of P. foetida. The hepatic, non-hepatic, antioxidant, and inflammatory parameters were estimated, as well as the mRNA expression. Results: Paederia foetida treatment remarkably suppressed the level of hepatic parameters such as alkaline phosphatase, alanine transaminase, aspartate aminotransferase; and non-hepatic parameters like creatinine, total protein, bilirubin, and blood urea nitrogen level at dose dependent manner. It also altered the level of antioxidant parameters such as lipid peroxidation, superoxide dismutase, glutathione peroxidase, glutathione, and catalase in the serum, as well as hepatic tissue, and also suppressed the level of cytokines such as tumor necrosis factor-α, interleukin-1β, interleukin-6; and inflammatory parameters such as cyclooxygenase-2, prostaglandin, and nuclear factor kappa B, respectively. Paederia foetida also altered the level of nuclear factor erythroid 2-related factor 2 (Nrf2) and heme oxygenase-1 (HO-1). Conclusion: Paederia foetida exhibited the hepatoprotective effect against paracetamol-induced hepatobiliary disease in rats via inflammatory and Nrf2/HO-1 pathway.